The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcph.1070
|View full text |Cite
|
Sign up to set email alerts
|

N‐Palmitoyl Ethanol Amide Pharmacological Treatment in Patients With Nonsurgical Lumbar Radiculopathy

Abstract: Palmitoyl ethanol amide (PEA) is an endogenous substance that plays a role in neuropathic pain. In this article, we evaluated both the safety and the efficacy of ultramicronized PEA (um-PEA) in the treatment of low back pain related to nonsurgical lumbar radiculopathy. In this prospective single-blind study, patients with low back pain related to nonsurgical lumbar radiculopathy received the fixed combination acetaminophen/codeine (500 mg + 30 mg/d) for 7 days, and then it was stopped and changed to um-PEA (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Previous studies reported that treatment with PEA does not cause adverse events or drug interactions and it doesn't induce pharmacological tolerance ( 16 , 35 – 37 ). Our data demonstrate that um-PEA chronically administered for 90 days and occasionally added on to NSAIDs significantly reduces the score of pain intensity, the number of attacks/month, and the days of pain during each attack irrespective to age and gender, suggesting a synergic effect of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that treatment with PEA does not cause adverse events or drug interactions and it doesn't induce pharmacological tolerance ( 16 , 35 – 37 ). Our data demonstrate that um-PEA chronically administered for 90 days and occasionally added on to NSAIDs significantly reduces the score of pain intensity, the number of attacks/month, and the days of pain during each attack irrespective to age and gender, suggesting a synergic effect of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The ultramicronized form makes the substance more effective and safer. Ultramicronized PEA (umPEA) has been shown to effectively reduce central and peripheral neuroinflammatory disorders such as migraine, neuropathies, and radiculopathies 4–7. The case offers two considerations: the late onset of BMS and the efficacy of PEA on pain-burning.…”
Section: Discussionmentioning
confidence: 99%
“…It has a structure similar to endocannabinoids, which are produced by the body to repair the damage caused by various pathological situations, thanks to their antioxidant, immunosuppressive, anti-inflammatory and painkiller activity. It has proved effective in neuropathic disorders and in migraine as demonstrated by the studies of Chirchiglia et al in 2016, 2017, and 2018 4–7…”
Section: Introductionmentioning
confidence: 97%
“…Pain can radiate down the back along a leg or foot, and this is described as sciatica, which can usually be reproduced with certain activities and positions, such as sitting or walking, and it is often caused by the compression of the lower spinal nerve roots (L5 and S1) [215]. Overall, several findings would suggest that PEA and PEA-um administration might be effective in the management of pain sciatic associated with lumbosciatalgia [216,217] or lumbar radiculopathy [218], and of pain associated to carpal syndrome [211,219,220]. Moreover, according to the literature, patients complain of pain and swelling as the main factors negatively influencing their quality of life [221] during postoperative course, as well as in patients suffering from neuropathic pain that is associated with pathologies of various etiologies [222], such as post-herpetic neuralgia.…”
Section: Clinical Studiesmentioning
confidence: 99%